2015
DOI: 10.21149/spm.v57i1.7398
|View full text |Cite
|
Sign up to set email alerts
|

Sensory evaluation of dairy supplements enriched with reduced iron, ferrous sulfate or ferrous fumarate

Abstract: Sensory evaluation of dairy supplements enriched with reduced iron, ferrous sulfate or ferrous fumarate. Salud Publica Mex 2015;57:14-21. Abstract Objective. To determine the degree of liking of the Oportunidades programme dietary supplements (DS) -purees and beverages-added with different iron salts (IS): reduced iron (RI), ferrous sulphate (FS) or ferrous fumarate (FF) during 24 weeks of storage. Materials and methods. The DS were evaluated through a hedonic scale for aroma, flavour and colour attributes; at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
2
0
2
Order By: Relevance
“…These results infer that it was the flavor that resulted in the low acceptability of this formulation, although it also received low scores for appearance and color when compared with the others. The final chocolate formulation had a high pH value and darkened similarly to that reported by Morales, S anchez-Vargas, García-Zepeda, and Villalpando (2015). The authors reported the development of an undesirable gray color in powdered, chocolate flavored nutritional mixes when fortified with iron, as also with ferrous fumarate and ferrous sulfate.…”
Section: Sensory Evaluationsupporting
confidence: 60%
“…These results infer that it was the flavor that resulted in the low acceptability of this formulation, although it also received low scores for appearance and color when compared with the others. The final chocolate formulation had a high pH value and darkened similarly to that reported by Morales, S anchez-Vargas, García-Zepeda, and Villalpando (2015). The authors reported the development of an undesirable gray color in powdered, chocolate flavored nutritional mixes when fortified with iron, as also with ferrous fumarate and ferrous sulfate.…”
Section: Sensory Evaluationsupporting
confidence: 60%
“…A technical report from the efficacy study described in Table 1 (18) showed that Nutrisano fortified with reduced iron had no impact on iron status or anemia after 4 mo follow-up compared with micronutrient syrup ( Table 2 ). In parallel, studies confirmed that both ferrous sulfate and reduced iron resulted in greater changes to organoleptic properties of the foods than ferrous gluconate (45), which then replaced reduced iron as a fortificant.…”
Section: Resultsmentioning
confidence: 82%
“…La evolución del contenido de sólidos solubles, pH y acidez del alimento pasteurizado durante el almacenamiento demuestra que el tratamiento [13] térmico permite mantener los valores iniciales de acidez y sólidos solubles durante 14 días (Figura 4) mientras que sin tratamiento se evidenciaron diferencias significativas a partir del día 7 (Figura 1).…”
Section: Discussionunclassified
“…En Colombia las principales matrices utilizadas en la fortificación voluntaria son los cereales para desayuno, las pastas y las bebidas, siendo las vitaminas A, C y B1 y los minerales hierro, zinc y calcio los nutrientes más adicionados 10 . En cuanto a la fortificación con hierro, se han desarrollado productos que incluyen refrescos de fruta (11) , yogurt (12) , suplementos alimenticios (papillas y bebidas) (13) , fórmulas infantiles (14) , entre otros. También se han realizado estudios de fortificación con hierro sobre matrices vegetales como trozos de calabaza procesados como snacks (15) .…”
Section: Introductionunclassified